PENEGAKAN HUKUM DALAM PERSPEKTIF AL-QURâAN - Yusuf, Ismail (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2015)
Holy Quran pay great attention to the issue of the rule of law as one ofÂ  the pillars to achieve ishlahal-afarat wa al-mujtamaâ, although in fact the Qurâan is not a book of statute law. So that the law can be enforced among men, the Qurâan has provided the principles of fundamental importance. The most fundamental principle of justice; whereas the other principle is the elaboration of the principles of justice.